Strategic Development of Village-Owned Enterprises for Enhancing Village Revenue - Kipkemboi Kandie; Bejo Mulyadi; Iwan Riady; Sujani Sujani (Economy and Finance Enthusiastic, 2025)
Village-Owned Enterprises (BUMDes) play a crucial role in driving rural economic development and supporting the financial independence of villages. However, many BUMDes, including in Suntalangu Village, face challenges in optimizing their potential to significantly contribute to Village Original Income (PADes). Addressing these issues is essential to ensure sustainable village-level economic growth and improve community welfare. This study aims to identify and formulate business development strategies for BUMDes Suntalangu to increase PADes. Using the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis method, the study evaluates internal and external factors influencing BUMDes performance. The analysis results indicate that while BUMDes has growth opportunities, existing weaknesses hinder its development. Proposed strategies to address these challenges include optimizing current assets, diversifying business activities based on untapped local potential, enhancing human resources through entrepreneurship training and education, and improving promotion and marketing through social media. The implementation of these strategies is expected to strengthen BUMDes' contribution to PADes and the economic welfare of the local community.